Carrier-Free Core-Shell NVTIA™ Tart Cherry-Celery Seed-Bromelain Nanocomposite for Uric Acid Metabolic Support: Formulation Characterization and Mechanistic Rationale - Yassine, Jabar; Semenza, Gregg L.; Vargas, Camila (International Journal of Public Health and Medical Research, 2026)
Background: Botanical approaches to hyperuricemia and gout remain attractive, but their practical performance is often limited by variable raw-material standardization, poor aqueous dispersion of lipophilic phytochemicals, and inconsistent clinical signals from single-ingredient cherry products. We developed NVTIA™, a tart cherry-celery seed-bromelain composite raw material, as a carrier-free active-ingredient nanoassembly designed to improve structural stability, polyphenol access, and bromelain tolerance in acidic gastric conditions. Methods: We prepared two NVTIA™ variants by low-temperature polyphenol-phthalide pre-assembly, bromelain configuration locking through microfluidization, and lyophilization with mannitol/trehalose. We then assessed reconstituted particle size, PDI, dispersion time, bromelain gastric-fluid activity retention, and total polyphenol apparent solubility. Results: NVTIA™-1 reconstituted to 112 nm nanoparticles with PDI 0.16, dispersed in 22 s, retained 89.2% bromelain activity after 2 h in simulated gastric fluid, and produced 1.57 mg/mL apparent total-polyphenol solubility. NVTIA™-2 reconstituted to 128 nm nanoparticles with PDI 0.18, dispersed in 25 s, retained 87.6% enzyme activity, and produced 1.82 mg/mL solubility. Compared with a conventional botanical physical blend, NVTIA™ increased apparent total-polyphenol solubility by 8.3-9.6 times and shortened dispersion time by 73.7-76.8%. Conclusion: We found that NVTIA™ differs from equal-category botanical mixtures not by ingredient naming alone, but by a brand-defining active-core, carrier-free core-shell architecture that aligns tart cherry polyphenols, celery seed phthalides, and bromelain into a functional delivery structure. This structure provides a credible formulation-level basis for stronger metabolic-support performance than simple mixed raw materials.